European consensus statement on leptospirosis in dogs and cats. (March 2015) - Schuller, S.; Francey, T.; Hartmann, K.; Hugonnard, M.; Kohn, B.; Nally, J. E.; Sykes, J.
<x xml:space="preserve">Abstract</x> Leptospirosis is a zoonotic disease with a worldwide distribution affecting most mammalian species. Clinical leptospirosis is common in dogs but appears to be rare in cats. Both dogs and cats, however, can shed leptospires in the urine. This is problematic as it can lead to exposure of humans. The control of leptospirosis, therefore, is important not only from an animal but also from a public health perspective. The aim of this consensus statement is to raise awareness of leptospirosis and to outline the current knowledge on the epidemiology, clinical features, diagnostic tools, prevention and treatment measures relevant to canine and feline leptospirosis in Europe.